Radiation-induced optic neuropathy: characteristic appearances on gadolinium-enhanced MR. - Hudgins, P A; Newman, N J; Dillon, W P; Hoffman, J C (American Journal of Neuroradiology, 1992)
PURPOSE To assess the value of contrast-enhanced MR in the evaluation of radiation-induced optic neuropathy.MATERIALS AND METHODS Three patients with rapid visual loss 1 1/2 to 3 years after radiation therapy to the optic nerves were studied with gadopentetate dimeglumine-enhanced MR images. All patients received over 5000 cGy, experienced rapid, permanent visual loss over several days to weeks, and underwent MR within weeks of presentation.RESULTS Enhanced MR images on each patient revealed focal discrete enhancement of the intracranial optic nerve. One patient underwent biopsy of the enhancing segment; this revealed pathologic changes of radiation optic neuropathy. Optic nerve enhancement in a patient with visual loss and a prior history of radiation therapy to the orbits or optic nerves suggests radiation optic neuropathy.CONCLUSION Contrast-enhanced MR of the orbits, optic nerves, and chiasm is the imaging test of choice in patients with vision loss after radiation therapy for sellar or skull base disease; MR findings may obviate the need for biopsy.